2020
DOI: 10.1093/emph/eoaa043
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting patterns of variation in human thyroid function

Abstract: Two hundred million people worldwide experience some form of thyroid disorder, with women being especially at risk. However, why human thyroid function varies between populations, individuals and across the lifespan has attracted little research to date. This limits our ability to evaluate the conditions under which patterns of variation in thyroid function are best understood as ‘normal’ or ‘pathological’. In this review, we aim to spark interest in research aimed at understanding the causes of variation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 178 publications
0
18
0
4
Order By: Relevance
“…Likewise, a single-nucleotide polymorphism in the DIO2 gene of Neanderthals [ 53 ] that resulted in a decreased capacity for conversion of T4 to T3 could have affected key developmental programmes and could potentially explain the significant phenotypical differences between Neanderthals and Homo sapiens despite their closeness in terms of genetic ancestry [ 53 , 54 ]. Most importantly, this variant may have enabled Neanderthals to hibernate and survive long and cold winters [ 55 ] (if this evidence is further confirmed), but when archaic humans switched to a high-carbohydrate diet, the variant became disadvantageous, as it is associated with an increased risk of diabetes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a single-nucleotide polymorphism in the DIO2 gene of Neanderthals [ 53 ] that resulted in a decreased capacity for conversion of T4 to T3 could have affected key developmental programmes and could potentially explain the significant phenotypical differences between Neanderthals and Homo sapiens despite their closeness in terms of genetic ancestry [ 53 , 54 ]. Most importantly, this variant may have enabled Neanderthals to hibernate and survive long and cold winters [ 55 ] (if this evidence is further confirmed), but when archaic humans switched to a high-carbohydrate diet, the variant became disadvantageous, as it is associated with an increased risk of diabetes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…TH, especially T3, inhibit TRH and TSH secretion [ 2 ]. However, very recently, the HPT axis has been suggested as a dynamic system with plasticity, allowing adaptation to demanding situations through regulating “life-history trade-offs between reproduction, growth, immunity and basal metabolic rate” in the setting of an evolutionary ecology framework [ 35 ].…”
Section: Synthesis Metabolism and Transport Of Thmentioning
confidence: 99%
“…The activity of TRH neurons is inhibited by negative energy balance situations such as fasting, inflammation or chronic stress [ 142 ]. Indeed, very recently, Keestra et al suggested an evolutionary ecology framework according to which HPT axis is considered a dynamic, adaptive system with a key role in “mediating life-history trade-offs between the functions of reproduction, growth, immunity and basal metabolic rate” [ 143 ] in the setting of demanding situations, including depression, psychosocial stress, and traumatic stress [ 144 , 145 ]. The absence of a causality between the psychosocial stress and the thyroid disorders in the setting of COVID-19 pandemic does not undermine the magnitude of an holistic approach to this issue, which will enable an integrated patient-oriented management of thyroid disorders, including DTC, during the challenging COVID-19 pandemic and beyond.…”
Section: Future Perspectivesmentioning
confidence: 99%